Effects of a Psychosocial Intervention on the Subjective Experiences of Children Living with Atopic Dermatitis: A Qualitative Study in Hong Kong - Qian-Wen Xie (MDPI AG, 2023)
Nonpharmaceutical interventions are important for addressing the psychosocial needs of children living with atopic dermatitis (AD). The current study aimed to investigate the effects of an integrative body-mind-spirit (IBMS) intervention on the subjective experiences of affected children and explore the mechanisms underlying the effects. Using a drawing-based, qualitative approach, the current study conducted two rounds of interviews with 13 children (aged 8-12 years) diagnosed with moderate or severe AD before and after they attended the IBMS intervention. Data were analyzed by using the thematic analysis method. The IBMS intervention worked by changing participants' perceptions at the cognitive level, improving their coping strategies at the behavioral level, and constructing their social support network at the environmental level. Cognitive, behavioral, and environmental factors might mediate the relationships between the IBMS intervention and participants' psychological and physical outcomes. This study highlighted the wider inclusion of child-centered qualitative research in the evaluation of the effects of psychosocial interventions designed for children.